The implementation of school based assessment in ESL classrooms: the case of secondary schools in Bintulu, Sarawak / Sheela Faizura Nik Fauzi - Nik Fauzi, Sheela Faizura (2016)
This research is carried out to investigate the implementation of school based assessment in ESL classroom in selected secondary schools in Sarawak. The geographical area chosen is Bintulu, Sarawak. The focus would be the eight secondary schools located there. The researcher employed mixed mode methodology which includes both qualitative and quantitative data collection. Qualitative data was gathered through document analysis, semi structured interviews and classroom observations. On the other hand, quantitative data was obtained using questionnaire. The study employs descriptive data analysis. The data analysis of research question 1 showed that the overall mean score for the perception towards teachers' readiness in implementing school based assessment was high (m=3.98, std dev=0.33). The teachers were ready to implement school based assessment but their students needed guidance in gearing up towards school based assessment. Data analysis of research question 2 showed that the overall mean score for the perception towards teachers' preparedness in implementing school based assessment was moderate (m=3.20, std dev=0.32). In research question 3, the result showed that the overall mean score for the challenges faced by the teachers in implementing school based assessment.was high (m=3.49, std dev=0.26). The internal challenges in implementing school based assessment in ESL classroom are preference on school based assessment, objectivity, extra workload and time constraint. Meanwhile, the external challenges in implementing school based assessment are poor internet connectivity, students' attitude and students' English language competency. Research question 4 involved classroom observations that reflected the standard operating procedures of school based assessment. The teachers were implementing school based assessment as depicted by school based assessment documents analysis. The school based assessments during classroom observation were aligned with the Ministry of Education guidelines. Research question 5 revealed students as excited and willing to accept school based assessment. But, they seemed to be receiving inadequate information on its proper implementation. The respondents had also made suggestions to improve school based assessment. Their suggestions were school based assessment needs to be more systematic, school should provide facilities and the system of school based assessment must be well maintained.